Prevalence and Predictors of “Small Size” Babies in Ethiopia: In-depth Analysis of the Ethiopian Demographic and Health Survey, 2011 - Alemu, Taddese (Ethiop J Health Sci, 2016)
BACKGROUND: Low Birth Weight (LBW) babies account for nearly 80% of neonatal deaths globally. In Ethiopia, only 5% of them are weighed at birth. This study analyzes the prevalence and key proximate determinants of reported infant size, and its validity to use as a proxy indicator for low birth weight inthe Ethiopian context. METHODS: In-depth analysis of the Ethiopian Demographic and Health Survey dataset was conducted using representative data collected from all regions in the country. Considering reported fetal size at birth as an outcome variable, key predicting variables from socio-demographic, household, child and obstetric characteristics were employed for analyses. Chi-square test and multivariate logistic regression model were used to determine predictors at p value < 0.05. RESULTS: An average of 29.1% of Ethiopian babies were reported “small” at birth in 2011. various variables from socio-demographic, household, child and maternal reproductive characteristics were identified as key predictors. Women who develop anemia and not attending antenatal care during pregnancy had 15% and 41% more risk of giving birth to the reported “small size” babies than their counterparts (AoR = 1.15, and 1.41, 95% CI (1.02, 1.64 and 1.06, 1.88) respectively. Maternal age at delivery, maternal literacy level, paternal educational status and presence of radio or television in the household and other factors were also other key predictors identified. CONCLUSION: The prevalence of small size babies in Ethiopia is high but comparable to regional estimates of LBW. It is recommend that improving maternal nutritional and socio-economic status is a timely intervention to tackle the problem.